Induction of defense-related enzymes in tomato plants inoculated with selected rhizobacteria against bacterial wilt disease - Yulmira Yanti; Hasmiandy Hamid; Yaherwandi Yaherwandi; Raflin Reflin (Universitas Lampung, 2026)
Bacterial wilt caused Ralstonia syzygii subsp. indonesiensis is one of the most destructive disease of tomato and results in severe yield losses. Plant growth-promoting rhizobacteria (PGPR) are known to enhance plant growth and health. In previous research, seven selected PGPR strains were identified for their ability to suppress R. syzygii subsp. indonesiensis and promote tomato growth. The present study aimed to evaluate the enzymatic defense responses of tomato plants inoculated with two selected rhizobacterial strains. The strains were assessed for their ability to induce the production of defense-related enzymes, including peroxidase (PO), phenylalanine ammonia-lyase (PAL), polyphenol oxidase (PPO), and lipoxygenase (LO). R. syzigii subsp. indonesiensis was inoculated onto tomato plants seven days after rhizobacterial treatment at the seedling stage. Enzyme activities were recorded from 0 to 30 days after pathogen inoculation at two-day intervals. The results showed a reduction in disease incidence and severity in tomato plants treated with the two rhizobacterial strains compared with the control. E. oryzendophyticus RZ.2.2.AG2 demonstrated greater effectiveness in reducing disease incidence (26%) and severity (2.5) than B. thuringiensis RZ.1.1.AG4. Enzyme activity assays further confirmed that both strains induced plant resistance by increasing PAL, PO, PPO, and LO activities, with significantly higher enzyme activity observed in roots than in leaves. Tomato plants treated with E. oryzendophyticus RZ.2.2.AG2 exhibited the highest enzyme activities in both roots and leaves, indicating that disease suppression was associated with induced systemic resistance (ISR) mediated through activation of defense-related enzymes.